Determination of energy dependent total macroscopic cross-sections of different materials using the Monte Carlo method - Atlı, Deniz (My University, 2023)
Nükleer bir reaksiyonda, nötronların çekirdeklerle etkileşim olasılığını santimetre başına ifade eden terim, reaksiyon tesir kesiti olarak bilinir. Nükleer tesislerin güvenli ve verimli çalışması için, güç santralleri, hızlandırıcılar, fisyon ve füzyon reaktörleri gibi tesislerde kullanılacak malzeme ile parçacıklar arasındaki tüm olası etkileşimlerin dikkate alınması önemlidir. Tesir kesiti verileri, endüstriyel ve tıbbi alanlarda radyoizotop üretimi, radyasyon tedavisi, zırhlama ve malzeme geliştirme gibi birçok alanda kullanılır. Bu nedenle, bir reaksiyonun tesir kesiti değerleri ve reaksiyon sonucunda ortaya çıkan parçacıkların enerji spektrumları, deneysel ve teorik yöntemlerle incelenmelidir. Tesir kesiti, nükleer reaktörlerde reaksiyon kontrolü ve zincirleme fisyon olayını gerçekleştirmek için önemli bir parametredir. Nükleer enerji ya da radyasyon üreten sistemleri analiz etmek için çeşitli radyasyon kod teknikleri kullanılmaktadır. Bu teknikler arasında Monte Carlo Simülasyon yöntemi kullanılmaktadır. MCNP (Monte Carlo N-Particle) simülasyon kodu, geniş enerji aralıklarındaki bir çok parçacık türünü izlemek için tasarlanmış, enerjisi sürekli olan, farklı geometrili, zamana bağımlı, Monte Carlo radyasyon taşıma kodudur. Literatürde deneysel verileri mevcut olan bazı elementlerinin izotoplarına yönelik farklı enerjilerde nötron parçacık girişli reaksiyonlarda tesir kesiti ve yayınlanma spektrumu hesaplamaları gerçekleştirilmiştir. Bazı elementlerin/ materyalerin deneysel veya teorik olarak enerjiye bağlı toplam makroskopik tesir kesitleri ise literatürde bulunmamaktadır. Bu tezde Monte Carlo N-Particle simülasyon bazı materyallerin (örneğin vermiculite, plexiglass, bor katkılı beton vb.) enerjiye bağlı makroskopik tesir kesitlerinin hesaplanması hedeflenmektedir. Bu tez çalışmasında öncelikle MCNPX koduyla yapılacak olan hesaplamaların geometrik deney düzeneği, data kartları ve yüzey kartları yardımıyla oluşturulacaktır. Daha sonra farklı enerjilerdeki nötron parçacıklarının ışın holünden geçirilmesiyle materyale çarpan nötronların bazıları saçılacak bazıları ise materyalin arkasında bulunan detektör tarafından tespit edilecektir. Dedektör olarak sıvı sintilatör detektörü koda yerleştirilecek olup, kullanılan materyal için kaydedilen nötron spektrumuna göre analizler yapılacak ve aynı zamanda farklı enerjilerdeki nötron makroskopik tesir kesitleri hesaplanacak ve daha sonra bu değerler grafiklere aktarılacaktır. Yapılan analizlerden elde edilen veriler literatürde mevcut olması durumunda deneysel verilerle karşılaştırılacaktır. Önümüzdeki yıllarda ülkemizde açılacak olan nükleer güç santrallerinde nötron kalkanı olarak kullanılabilecek malzemeler için öneride bulunulacaktır.

When a neutron beam passes through a material, it can undergo various interactions with the particles that make up the material. These interactions can lead to neutron scattering, reduction, or absorption under different conditions. The likelihood of a specific interaction occurring for a particular element can be determined by its cross section. The total cross section of all these interactions, including absorption, scattering, and others, is referred to as the total microscopic cross-section. The reaction cross-section is the probability of neutron-nuclear interaction per centimeter of neutron motion in a nuclear reaction. In order to provide safe and suitable conditions in nuclear facilities such as nuclear power reactors, accelerators, all interactions between the material to be used and the particles must be considered. Cross section data; it is used in a wide range of areas such as radioisotope production, radiation therapy, shielding and material development for industrial and medical fields. Hence, it is imperative to explore the cross-sectional values of a reaction and the energy distributions of particles emitted during the reaction through both experimental and theoretical approaches, particularly in the contexts of radiation therapy, as well as the development of shielding materials for applications in industrial and medical sectors. The cross section is an important parameter for reaction control and chain fission in nuclear reactors. Various radiation code techniques are used to analyze nuclear energy or radiation generating systems. Among these techniques, Monte Carlo Simulation method is used. MCNP (Monte Carlo N-Particle) simulation code is a constant energy, time-dependent, ww wwy Monte Carlo radiation transport code with different geometry, designed to track many types of particles in wide energy ranges. For the isotopes of some elements whose experimental data are available in the literature, cross-section and emission spectrum calculations have been carried out in reactions with neutron particle input at different energies. The total macroscopic cross-sections of some elements/ materials, depending on the experimental or theoretical energy, are not available in the literature. In this thesis, it is aimed to calculate the energy-dependent macroscopic cross-sections of some materials (for example, vermiculite, plexiglass, reinforced concrete, etc.) with the Monte Carlo N-Particle simulation program. In this thesis, first of all, the calculations to be made with the MCNPX code will be created with the help of the geometric experimental setup, data cards and surface cards. Then, by passing neutron particles of different energies through the beam hall, some of the neutrons hitting the material will be scattered, and some will be detected by the detector located behind the material. A liquid scintillator detector will be placed in the code as a detector, analyzes will be made according to the recorded neutron spectrum for the material used, and at the same time, the macroscopic cross-sections of neutrons at different energies will be calculated and then these values will be plotted. If the data obtained from the analyzes are available in the literature, they will be compared with the experimental data. Suggestions will be made for materials that can be used as neutron shields in nuclear power plants to be opened in our country in the coming years.
Farklı materyalleri̇n enerji̇ye bağlı toplam makroskopi̇k tesi̇r kesi̇tleri̇ni̇n Monte Carlo yöntemi̇yle beli̇rlenmesi̇
Keywords: buildup factor; Fizik; MCNP simulation; MCNP simülasyon; Physics; Toplam makroskopik tesir kesiti; toplam tesir kesiti; total cross section; yığılma faktörü Total macroscopic cross section